2016
DOI: 10.1111/1758-2229.12444
|View full text |Cite
|
Sign up to set email alerts
|

Genomic, transcriptomic and proteomic analyses of Dehalobacter UNSWDHB in response to chloroform

Abstract: Organohalide respiring bacteria (ORB) are capable of utilising organohalides as electron acceptors for the generation of cellular energy and consequently play an important role in the turnover of natural and anthropogenically-derived organohalides. In this study, the response of a Dehalobacter sp. strain UNSWDHB to the addition of trichloromethane (TCM) after a 50 h period of its absence (suffocation) was evaluated from a transcriptomic and proteomic perspective. The up-regulation of TCM reductive dehalogenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…During the final days prior to harvest, CF dechlorination rate was 6.5 × 10 ‐11 mol cell −1 day −1 and the cell density was (9.8 ± 4.3) × 10 7 cells ml −1 . Before harvesting, we examined the expression of tmrA gene, as it was previously shown that the same gene is expressed upon CF respiration (Jugder et al ., ). To confirm the induction of tmrA at the gene level, transcription of tmrA gene was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the final days prior to harvest, CF dechlorination rate was 6.5 × 10 ‐11 mol cell −1 day −1 and the cell density was (9.8 ± 4.3) × 10 7 cells ml −1 . Before harvesting, we examined the expression of tmrA gene, as it was previously shown that the same gene is expressed upon CF respiration (Jugder et al ., ). To confirm the induction of tmrA at the gene level, transcription of tmrA gene was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…strain UNSWDHB is able to use CF as a terminal electron acceptor for growth. It has previously been demonstrated that the enzyme directly responsible for reductive dechlorination of CF is the membrane‐associated TmrA, which is specifically overproduced in response to CF (Jugder et al ., ; Wong et al ., ). In this study, we for the first time report the production, purification and biochemical characterization of a chloroform‐reducing enzyme.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Complete or partial WLP encoding genes have been reported in other OHRB, including: Dehalobacter restrictus strains PER-K23 and UNSWDHB (Kruse et al, 2013; Rupakula et al, 2013; Jugder et al, 2016b; Wong et al, 2016) among others. The WLP pathway can function in either reductive or oxidative directions.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we first explored the metabolic dependency of Dhb using its genome-scale metabolic model (Correia et al ., 2018), which was built based on a highly annotated and experimentally refined Dhb genome (Wang et al, 2016), along with shared expression patterns in proteomic datasets of Dhb strains PER-K23, UNSWDHB, DCA and CF (Jugder et al ., 2016, Rupakula et al ., 2013, Rupakula et al ., 2015, Tang and Edwards, 2013a). The model simulations consider cofactor availability, enzyme promiscuity, physiological redox conditions, and further model constraints based on experimental values obtained in this study.…”
Section: Introductionmentioning
confidence: 99%